Postoperative Radiotherapy Improved Survival of Poor Prognostic Squamous Cell Carcinoma Esophagus - Chen, Junqiang; Zhu, Ji; Pan, Jianji; Zhu, Kunshou; Zheng, Xiongwei; Chen, Mingqiang; Wang, Jiezhong; Liao, Zhongxing (The Annals of thoracic surgery, 2010)
The purpose of this study was identify prognostic factors and to investigate the association between postoperative radiotherapy and overall survival of thoracic esophageal squamous cell carcinoma patients. From January 1993 to March 2007, 1,715 patients underwent extended esophagectomy with three-field lymph node dissection with or without postoperative radiotherapy and were eligible for analysis. Patients were grouped to surgery only (n = 1,277) and surgery plus postoperative radiotherapy (n = 438). Radiation dose was 50 Gy in 25 fractions. The overall survival rates at 1, 3, 5, and 10 years were 86.6%, 61.3%, 49.4%, and 36.1%, respectively. Univariate and multivariate analyses showed that age 60 years or more, male sex, tumor more than 5 cm long, poorly differentiated histology, T4 tumor, presence of a vascular cancer thrombus in the surgical specimen, lymph node positivity, 3 or more positive lymph nodes, and disease stage II or higher were negative prognostic factors for overall survival. Postoperative radiation therapy improved overall survival for patients with poor disease-related prognostic factors: positive nodal disease, 3 or more positive lymph nodes, stage III/IV, and large or deeply invading tumor. Postoperative radiation had no survival benefit for patients who did not have the poor disease-related prognostic factors. Postoperative radiotherapy is indicated for patients with poor disease-related prognostic factors.